2012
DOI: 10.1002/jcp.24130
|View full text |Cite
|
Sign up to set email alerts
|

Influence of fatty acid‐free diet on mammary tumor development and growth rate in HER‐2/neu transgenic mice

Abstract: Numerous investigations have found a relationship between higher risk of cancer and increased intake of fats, while results of clinical studies of fat reduction and breast cancer recurrence have been mixed. A diet completely free of fats cannot be easily administered to humans, but experimental studies in mice can be done to determine whether this extreme condition influences tumor development. Here, we examined the effects of a FA-free diet on mammary tumor development and growth rate in female FVB-neu proto-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…Furthermore, consumption of eicosapentaenoic acid drastically reduced serum leptin levels. Another dietary intervention study on this transgenic mouse model observed that a fatty acid-free diet reduced tumor incidence and delayed tumor appearance but tumor growth rate was unaffected [144]. A recent report has shown that caloric restriction elicited an increase in mammary ERα and ERβ expression in MMTV-neu transgenic mice in comparison with overweight (high-carbohydrate, low-fat diet) and diet-induced obesity (high-carbohydrate, high-fat diet) regimen [145].…”
Section: Results Of In Vivo Experimentsmentioning
confidence: 84%
“…Furthermore, consumption of eicosapentaenoic acid drastically reduced serum leptin levels. Another dietary intervention study on this transgenic mouse model observed that a fatty acid-free diet reduced tumor incidence and delayed tumor appearance but tumor growth rate was unaffected [144]. A recent report has shown that caloric restriction elicited an increase in mammary ERα and ERβ expression in MMTV-neu transgenic mice in comparison with overweight (high-carbohydrate, low-fat diet) and diet-induced obesity (high-carbohydrate, high-fat diet) regimen [145].…”
Section: Results Of In Vivo Experimentsmentioning
confidence: 84%
“…Different effects of SFAs, such as PA, and MUFAs, have been reported on cell proliferation and tumor development also in in vitro and animal studies [110,111]. The conflicting results may be due to a combined administration in animals of different FAs.…”
Section: Palm Oil and Palmitic Acid: Role In Cancermentioning
confidence: 99%
“…Interestingly, Rossini et al demonstrated in mice that a FA-free diet reduces mammary tumor incidence but not tumor growth rate [111]. Because humans are not able to comply with a FA-free diet, Rossini’s study suggests that a low-fat diet might play a protective role in tumorigenesis but no effects should be expected on already established tumor masses.…”
Section: Palm Oil and Palmitic Acid: Role In Cancermentioning
confidence: 99%
“…Epidemiological studies strongly suggest an association between a higher intake of dietary fat and obesity with an increased risk of developing breast cancer. Moreover, obesity is characterized for an elevation of circulating free fatty acids (FFAs) (1, 2, 3, 4). FFAs are an energy source, and induce activation of signal transduction pathways in breast cancer cells (5, 6, 7, 8).…”
Section: Introductionmentioning
confidence: 99%